Responsive Aggression Regulation Therapy (Re-ART): An Evaluation Study in a Dutch Juvenile Justice Institution in Terms of Recidivism - Hoogsteder, Larissa M. (International journal of offender therapy and comparative criminology, 2018)
This article describes a quasi-experimental study of the effectiveness of Responsive Aggression Regulation Therapy (Re-ART) in terms of recidivism for 16- to 21-year-old juveniles with aggression problems and high risk of recidivism. In a Dutch juvenile justice institution, an experimental group received Re-ART (n = 63, Re-ART group) and a waitlist control group received Treatment as Usual (n = 28, TAU group). Results indicated that Re-ART is significantly more effective than TAU in reducing the juveniles' recidivism risk for violent offending. Compared with the TAU group, the Re-ART group showed significantly less violent crimes after 2 and 3 years, less property crimes after 2 years, and less general recidivism after 2 and 3 years. There was no significant difference between groups in recidivism of property crimes with violence. Ethnicity, mild intellectual disabilities, substance abuse, and age did not moderate the effects on recidivism outcome, which indicates that Re-ART was equally effective for various groups.